State Medicaid Expansion and the Self-Employed - Jun Yeong Lee; John V. Winters (Institute of Labor Economics (IZA), 2020)
This paper examines effects of state Medicaid Expansion via the Affordable Care Act on the self-employed. We first examine impacts on the probability of self-employment and find no significant effect. We then examine the probability of having health insurance and the type of coverage for self-employed persons. Medicaid expansion increased overall health insurance coverage rates, with especially large impacts for the unincorporated self-employed. Medicaid expansion also increased the probability of Medicaid coverage as expected, but there is evidence of crowd out of other types of coverage. Impacts on health insurance rates of the self-employed also strengthened over time.
Keywords: H51; I13; L26; 330; health insurance; self-employed; Affordable Care Act; state Medicaid expansion